Urgensi Bimbingan dan Konseling di Lembaga Pendidikan Anak Usia Dini (Studi Paud dan TK di Kota Tasikmalaya) - oki lukman (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
The purpose of this study is to obtain an in-depth picture of the urgency of counseling and guidance services in early childhood education. This research is motivated by the opportunity for guidance and counseling to enter early childhood education institutions that are close or less close to the stage of early childhood education, this happens because early childhood education institutions do not understand the importance of guidance and counseling and do not understand the concept of implementing guidance and counseling. The data collection technique was carried out through a survey in the form of a questionnaire. The population in this study were PAUD teachers in Tasikmalaya City. The results showed that the distribution of scores for categorizing teacher response data on the importance of implementing guidance and counseling services carried out in early childhood education consisted of two categories, namely the unimportant category of 0% or as many as 0 respondents, then the important category was 100% or as many as 45 respondents. And the results of research on the implementation of guidance and counseling services carried out in early childhood education are divided into three categories, namely the frequent category of 15.55% or as many as 7 respondents, then the occasional category of 40% or as many as 18 respondents, and the never category. 44,44% or as many as 20 respondents